Robust Control of Nonlinear Jump Parameter Systems Governed by Uncertain Chains - Ford, J.J.; Ugrinovskii, V.A. (IEEE transactions on automatic control, 2008)
We consider an infinite-horizon minimax optimal control problem for stochastic uncertain systems governed by a discrete-state uncertain continuous-time chain. Using existing risk-sensitive control results, a robust suboptimal absolutely stabilizing guaranteed cost controller is constructed. Conditions are presented under which this suboptimal controller is minimax optimal. We then present a numeric algorithm for calculating a robust (sub)optimal controller using a Markov chain approximation technique.